Textual Perspectives on Prehistoric Contacts: Some Considerations on Female Death Demons, Heroic Ideologies and the Notion of Elite Travel in European Prehistory - Egeler, Matthias (The journal of Indo-European studies, 2009)
In 2005, Kristiansen and Larsson proposed a reconstruction of the European Bronze Age as an epoch characterised by a heroic ideology and long-distance travels of warrior-aristocrats. The present article comments on the general plausibility of this hotly debated theory from an inter-disciplinary perspective. Reviewing some results of on-going work on the early Irish, Norse, Etruscan and Greek demonologies of death, it notes that the combination of the motifs of the female bird-shaped demon, her functioning in the transition to a blissful afterlife and her marked sexuality reoccurs throughout early European demonologies with a frequency which might be taken to indicate a (pre-)historical connection between the corresponding figures. The complete lack of meaningful archaeological evidence for the respective demons in most of north-western Europe precludes a strictly archaeological tracing of the route of transmission of such figures. Yet the particular nature of the phenomenon suggests a transmission based on circumstances strikingly similar to those which Kristiansen and Larsson suggested for the European Bronze Age. As such conclusions have been reached on the basis of material entirely distinct from the data used by Kristiansen and Larsson, this might giv e some support to the general notion of the reconstruction of a ‘heroic (Bronze) Age’ in European prehistory.